18F-FDG PET/CT Metabolic Response With Hormone Receptor–Positive, Human Epidermal Growth Factor Receptor 2–Negative Breast Cancer Treated With Cyclin-Dependent 4/6 Kinase Inhibitors. (5th September 2022) - Filizoglu, Nuh; Ozguven, Salih; Erdil, Tanju Yusuf
Abstract: Dysregulation of the cyclin D–CDK4/6–INK4–RB pathway, which leads to uncontrolled cell proliferation, is frequently observed in breast cancer. Recently, 3 CDK4/6 inhibitors have been FDA approved as first-line treatment for patients with hormone receptor–positive, human epidermal growth factor receptor 2–negative advanced breast cancer. Despite promising clinical results, the metabolic response to treatment with these new drugs has not been elaborately demonstrated yet. Herein, we presented a patient with hormone receptor–positive, human epidermal growth factor receptor 2–negative breast cancer who demonstrated a complete metabolic response on 18 F-FDG PET/CT to treatment with a CDK4/6 inhibitor (ribociclib).